Tingkat Kecemasan dan Transendensi Orang Tua di Era Digital Pasca Pandemi COVID-19 - Elfan Fanhas Fatwa Khomaeny; Maesaroh Lubis; Maulidya Ulfah; Nur Hamzah (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
The Covid-19 pandemic, which requires all students to study online, has had an impact on many parents who experience difficulties in adapting to these changes, so many parents fall into anxiety conditions ranging from low levels (mild anxiety) to severe levels (severe anxiety), which if not managed properly can result in the next level such as stress, paranoia, depression, and other psychological impacts. The aim of carrying out this research is to check the level of anxiety and transcendence of parents. This research is classified as a quantitative type of research, with a total research sample of 6635 parents. Data was collected using a questionnaire with a research instrument consisting of 42 questions. The data obtained in the research was then analyzed using quantitative analysis. The results of the data analysis show that the anxiety level is at a high level, namely 80.77%, while the digital transcendence level is 57.42%, and the spiritual transcendence level is 91.77%. The high and low anxiety levels are directly proportional to parental transcendence, where there is a balance between digital and spiritual transcendence.